(3HQfGeL ebJQM bGFe Ydi GdJYde GdeOeL dJfejI egGQGJ GdGSJNOGe GdBef ddEfJQfJ h GdhYi HCNdGbjGJ GdJcfhdhLjG GdeYGUQI dOi JdGejP GdMdbI GdEYOGOjI (B/ s - (3CejQI QVG eSYO GdSYjOs; (3MSf MSjfi LGeY (B: s; (3efGd YHOGdYGd eHGQR (B: s ((3GdbGgQI (B: s (3CejQI QVG eSYO GdSYjO (B: s, 2015)
(3gOa GdHMK Gdi bjGS aGYdjI HQfGeL bGFe Ydi GdJYde GdeOeL ai JfejI egGQGJ GdGSJNOGe GdBef ddEfJQfJ h GdhYi HCNdGbjGJ GdJcfhdhLjG GdeYGUQI dOi JdGejP GdMdbI GdEYOGOjI(B. (3h dJMbjb gPG GdgOa Je JMOjO egGQGJ GdGSJNOGe GdBef ddEfJQfJ HGdMdbI GdEYOGOjI h dJfejI gPg GdegGQGJ Je JUeje HQfGeL ddJYdje GdeOeL HfXGe (B((3ehOjd(B)(3dEOGQI GdJYde GdEdcJQhfi h JWHjbg Ydi eLehYJjf JLQjHjI h VGHWI (B(36 (3JdejP Hcd eLehYI(B) (3HeOQSI CMeO Rhjd ddJYdje GdCSGSi HeOjfI OejGW GdLOjOI HeMGaXI OejGW(B. (3ceG Je JWHjb COhGJ GdHMK bHdjG h HYOjG Ydi JdGejP eLehYJj GdHMK h HYO GdJMdjd GdEMUGFi Je GdJhUd Gdi aGYdjI GdHQfGeL ai JfejI egGQGJ GdGSJNOGe GdBef ddEfJQfJ h GdhYi HCNdGbjGJ GdJcfhdhLjG GdeYGUQI dOi JdGejP GdMdbI GdEYOGOjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddJQHjI (B- (3bSe JcfhdhLjG GdJYdjes
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdGSJNOGe GdBef ddEfJQfJs; (3GdHQfGeL GdebJQMs; (3GdJYde GdeOeLs